Voltage Reduction in Medium Voltage Distribution Systems Using Constant Power Factor Control of PV PCS - Daisuke Iioka; Takahiro Fujii; Toshio Tanaka; Tsuyoshi Harimoto; Junpei Motoyama (Energies, 2020)
Reverse power flow from a photovoltaic (PV) system in a distribution system causes a voltage rise. A relative study regarding the reduction in the distribution feeder voltage depending on system conditions and the magnitude of reverse power flow has been conducted. Several methods for mitigating voltage rise have been proposed; however, the influence of these methods on the voltage in the distribution system, where the voltage is reduced due to reverse power flow, remains to be determined. In this study, the effect of constant power factor control in low-voltage PV systems, which are widely used as voltage rise countermeasures in distribution systems, was analyzed under the condition that the distribution line voltage decreases due to reverse power flow. Consequently, the constant power factor control of the low-voltage distribution system was found to adversely reduce voltage in the medium voltage distribution system due to the consumption of lagging reactive power by the PV systems.